Congenital Anomalies in Children of Mothers Taking Antiepileptic Drugs with and without Periconceptional High Dose Folic Acid Use: A Population-Based Cohort Study. - Lu Ban; Kate M Fleming; Pat Doyle; Liam Smeeth; Richard B Hubbard; Linda Fiaschi; Laila J Tata (PLoS ONE)
Background Antenatal antiepileptic drug (AED) use has been found to be associated with increased major congenital anomaly (CA) risks. However whether such AED-associated risks were different according to periconceptional high dose (5mg daily) folic acid supplementation is still unclear. Methods We included 258,591 singleton live-born children of mothers aged 15-44 years in 1990-2013 from The Health Improvement Network, a large UK primary care database. We identified all major CAs according to the European Surveillance of Congenital Anomalies classification. Absolute risks and adjusted odds ratios (aOR) were calculated comparing children of mothers prescribed AEDs to those without such prescriptions, stratified by folic acid prescriptions around the time of conception (one month before conception to two months post-conception). Results CA risk was 476/10,000 in children of mothers with first trimester AEDs compared with 269/10,000 in those without AEDs equating to an aOR of 1.82, 95% confidence interval 1.30-2.56. The highest system-specific risks were for heart anomalies (198/10,000 and 79/10,000 respectively, aOR 2.49,1.47-4.21). Sodium valproate and lamotrigine were both associated with increased risks of any CA (aOR 2.63,1.46-4.74 and aOR 2.01,1.12-3.59 respectively) and system-specific risks. Stratification by folic acid supplementation did not show marked reductions in AED-associated risks (e.g. for CAs overall aOR 1.75, 1.01-3.03 in the high dose folic acid group and 1.94, 95%CI 1.21-3.13 in the low dose or no folic acid group); however, the majority of mothers taking AEDs only initiated high dose folic acid from the second month of pregnancy. Conclusions Children of mothers with AEDs in the first trimester of pregnancy have a 2-fold increased risk of major CA compared to those unexposed. We found no evidence that prescribed high dose folic acid supplementation reduced such AED-associated risks. Although statistical power was limited, prescribing of folic acid too late for it to be effective during the organogenic period or selective prescribing to those with more severe morbidity may explain these findings.